Phenotypic variations of naturally grown Iris persica L. accessions as revealed using multivariate analytical methods - Ali Khadivi; Alireza Khaleghi; Yazgan Tunç (PLoS ONE, 2026)
Iris persica L. is a high-value ornamental species naturally distributed across montane regions of Iran, yet its intraspecific morphological variation remains underexplored. Understanding phenotypic diversity among wild accessions is critical for identifying superior genotypes suitable for conservation and horticultural breeding. This observational study was conducted on 78 naturally occurring I. persica accessions collected from seven ecogeographical regions of Markazi Province, Iran. Each accession represented a single independently growing individual plant, and 39 morphological and colorimetric traits were evaluated using multivariate statistical analyses. The results revealed considerable variation among accessions. Descriptive statistics showed that flower diameter ranged from 34.52 to 80.56 mm, fall length from 35.39 to 57.70 mm, and spathe length from 25.86 to 64.56 mm. Principal component analysis identified ten principal components explaining 82.46% of the total variation, with the first component (33.30%) driven primarily by flower size, fall length, and spathe length. The heatmap analysis clustered accessions into four distinct morphological groups, indicating clear phenotypic differentiation. Correlation analysis revealed significant positive associations between flower diameter and flower surface ( r = 0.87, p < 0.01), fall length and flower surface (r = 0.76, p < 0.01), and flower diameter and flower length ( r = 0.76, p < 0.01). Stepwise regression analysis indicated that fall length, flower diameter, and spathe length were key predictors of flower diameter. This study demonstrates extensive morphological diversity in I. persica , providing a strong basis for the selection of superior genotypes for ornamental breeding programs. Accessions such as ‘Alibolaghi-6’, ‘Sorkhe-4’, ‘Sorkhe-14’, ‘Shahbaz-11’, ‘Sorkhe-11’, ‘Sorkhe-12’, ‘Sorkhe-6’, ‘Palangdarreh-8’, ‘Sorkhe-5’, and ‘Bolagh-8’ exhibited outstanding floral characteristics and are recommended as potential candidates for future cultivar development and conservation strategies.